1984
DOI: 10.1007/bf00555223
|View full text |Cite
|
Sign up to set email alerts
|

Role of training dose in discrimination of nicotine and related compounds by rats

Abstract: Rats were trained to discriminate nicotine from saline in a two-bar operant conditioning procedure with food reinforcement. There was partial generalization to the nicotine analogues anabasine and cytisine in rats trained to discriminate either 0.2 or 0.4 mg/kg nicotine from saline. However, generalization was complete in rats trained to discriminate 0.1 mg/kg nicotine and, in a novel procedure, any one of three doses of nicotine (0.1, 0.2, or 0.4 mg/kg). There was no generalization to the muscarinic-cholinerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
104
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(118 citation statements)
references
References 15 publications
12
104
2
Order By: Relevance
“…The ED 50 for amphetamine (0.281 mg/kg) was also within the range described in operant drug discrimination experiments employing a 1 mg/kg training dose (0.26 mg/kg and 0.40 mg/kg (Young et al, 1998)]. Also similar to previous findings using operant drug discrimination procedures, CDP did not substitute for any of the stimulants that we trained as drug features (eg Stolerman et al, 1984), nor did any stimulant substitute for CDP (eg Gauvin et al, 1994). Finally, nicotine and amphetamine partially substituted for one another, although only 0.2 mg/kg nicotine statistically differed from saline controls (for similar findings in operant drug discrimination studies, see Bardo et al, 1997;Chance et al, 1977;Li and McMillan, 2003;Mansbach et al, 1998;Stolerman, 1989).…”
Section: Discussionsupporting
confidence: 84%
“…The ED 50 for amphetamine (0.281 mg/kg) was also within the range described in operant drug discrimination experiments employing a 1 mg/kg training dose (0.26 mg/kg and 0.40 mg/kg (Young et al, 1998)]. Also similar to previous findings using operant drug discrimination procedures, CDP did not substitute for any of the stimulants that we trained as drug features (eg Stolerman et al, 1984), nor did any stimulant substitute for CDP (eg Gauvin et al, 1994). Finally, nicotine and amphetamine partially substituted for one another, although only 0.2 mg/kg nicotine statistically differed from saline controls (for similar findings in operant drug discrimination studies, see Bardo et al, 1997;Chance et al, 1977;Li and McMillan, 2003;Mansbach et al, 1998;Stolerman, 1989).…”
Section: Discussionsupporting
confidence: 84%
“…Each of these 3 training doses has served as a discriminative stimulus for rats in a 2-lever operant drug discrimination task (Chance et al, 1977, Desai et al, 2003, Gasior et al, 1999, Morrison and Stephenson, 1969and Stolerman et al, 1997. In this task, completion of a response requirement on one lever results in reinforcement, whereas responses on the other lever result in no reinforcement (Gasior et al, 2000, Gasior et al, 2002, Morrison and Stephenson, 1969, Stolerman, 1989and Stolerman et al, 1984. On intermixed vehicle sessions, responding on the opposite lever is reinforced.…”
Section: Discussionmentioning
confidence: 99%
“…The case for asymmetry should perhaps not be overstated, as earlier studies have reported both full and partial substitution by dopamine compounds in nicotine-trained subjects (Desai et al, 1999;Gasior et al, 1999;Mansbach et al, 1998) (Wiley et al, 2002;Young and Glennon, 2002) and both full and partial substitution by nicotine in other dopaminergic psychostimulants (de la Garza and Johanson, 1983;1985;Desai et al, 1999;Desai et al, 2003). It is important to note that the degree of cross-substitution between methamphetamine and nicotine could be determined by training dose, as different patterns of stimulus control can be seen between groups trained to discriminate a high or a low dose of drug (Koek and Slangen, 1982;Stolerman et al, 1984). This effect is more pronounced when there are differences in mechanism or degree of efficacy between the compounds being tested, as is the case for methamphetamine and nicotine.…”
Section: Cross-substitutionmentioning
confidence: 91%